Effect of site selection on dielectric properties of Fe doped CaCu 3Ti4O12 electro-ceramic synthesized by citrate nitrate gel route - Singh L.; Mandal K.D.; Rai U.S.; Rai A.K. (My University, 2025)
The effect of doping of Fe at Cu2+ and Ti4+ sites in calcium copper titanate, CaCu3Ti4O12, has been examined. The compositions CaCu3-xFexTi4O 12 (CCFTO) and CaCu3Ti4-xFexO 12 (CCTFO), (x = 0.10) have been synthesized by citrate nitrate gel route. XRD analysis confirms the formation of single- phase ceramics on sintering at 900°C for 8 h. Structure of CaCu3Ti 4O12 does not change on doping with iron on Cu-site or Ti-site and it remains cubic. Surface morphology indicates that the average grain size is in range of 30-90 μm and 5-7 μm for systems CCFTO and CCTFO, respectively. EDX studies confirm the presence of Ca2+, Cu 2+, Ti4+ and Fe3+ ions as per stoichiometry of ceramics. The grain resistance of CCTFO is higher than that of CCFTO. Values of dielectric constant (εr) and dielectric loss (tanδ) of CCTFO are higher than those of CCFTO ceramic at all measured frequencies and temperatures. © 2014 Indian Association for the Cultivation of Science.